Correlation between decreased PaCO2 and thrombus site and 90d prognosis in patients with acute pulmonary embolism - Yang, Danrong; Liu, Yi (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to investigate the correlation between decreased partial pressure of arterial carbon dioxide (PaCO2) and thrombus location, as well as its association with 90-day prognosis in patients with acute pulmonary embolism (PE).MethodA retrospective analysis was conducted on the risk factors, clinical characteristics, and diagnostic findings of PE patients presenting with decreased PaCO2 at our hospital.ResultsMultivariate logistic regression analysis revealed that decreased PaCO2 in PE was significantly associated with thrombosis in the right pulmonary artery, thrombosis in the left lower lobe pulmonary arteries, and pulmonary hypertension (PH). Pearson correlation analysis showed a weak negative correlation between decreased PaCO2 and PASP and PVOI. Spearman correlation analysis indicated a weak negative correlation between decreased PaCO2 and computed tomography severity (CTS)-defined risk PE. Kaplan–Meier survival analysis demonstrated that decreased PaCO2 was not associated with 90-day mortality (χ2 = 0.263, p = 0.608).ConclusionA significant proportion of PE patients presented with decreased PaCO2, which was correlated with thrombosis in the right pulmonary artery and left lower lobe pulmonary arteries. However, decreased PaCO2 was not associated with 90-day mortality in PE patients.